Transcriptomic profiles reveal hormonal regulation of sugar-induced stolon initiation in potato - Xiaoqing Wang; Kaifeng Zheng; Tiancang Na; Guangji Ye; Shengcheng Han; Jian Wang (Scientific Reports)
Abstract Potato (Solanum tuberosum L.) is one of the world’s most important non-cereal food crops, with stolon development playing a crucial role in determining tuber yield. While some studies have examined the effects of sugars on potato stolon growth, their influence—particularly that of sucrose—on early stolon development remains unclear. Furthermore, the regulatory role of plant hormones in this process has yet to be established. Using a combination of in vitro culture, transcriptomics, gene expression analysis, and biochemical approaches, we investigated the contribution of sucrose (3% or 8%) on potato seedling stem nodes and stolon initials through phenotypic observation, RNA sequencing (RNA-seq), comparison of expression patterns, and hormone quantification. Firstly, compared to other types of sugars, we found that high concentrations of sucrose were the most effective in inducing stolon initial formation in potato seedlings. Furthermore, RNA-seq data showed that high sucrose levels significantly up-regulated the expression of genes involved in sugar metabolism and plant hormone metabolism. Additionally, the development of stem nodes and stolon initials under high sucrose conditions was also closely linked to hormone metabolism. Notably, high sucrose concentrations contributed to stem node and stolon initial development by modulating the IAA, CK, and GA signaling pathways. Based on the endogenous hormone measurement, and exogenous hormone application, together with heterologous overexpression of a potato Auxin response factor 9 (StARF9), we concluded that the early development of potato stolons was regulated by plant hormones, particularly auxin. In summary, this study elucidates the hormonal regulation of stolon initiation under high sucrose concentrations, offering a theoretical foundation and potential targets for in vitro culture and genetic improvement of potato.